Acceptance of Construction Scheduling Visualizations: Bar-charts, Flowline-charts, Or Perhaps BIM?. (2016) - Rolfsen, Christian Nordahl; Merschbrock, Christoph
Abstract: Four-dimensional Building Information Modelling is widely viewed as the next evolutionary step in construction scheduling. Linking scheduling information to parametric object models is believed to assist a more intuitive understanding of what is to be built when. We explore how 4D BIM, as a new method of visualization, compares to other pre-existing forms of visualization like bar- and flowline- charts. Based on a series of individual and focus group interviews, this paper reports construction professionals' perceptions of the utility of the different visualization methods. Simultaneously exposed to three types of scheduling of the same building, construction professionals evaluated their ease of use and usefulness. This was done based on the Technology Acceptance Model, which explains how individuals develop an intention to use technology. Based on this work we found the three scheduling methods having strengths and weaknesses. Gantt provides the simplicity and responsiveness required for the day-to-day communication in projects, and was perceived as the easiest to use. Flowline was perceived as less intuitive; however, some argued that it provides a better overview when many different work activities need to be run concurrently. 4D BIM has the clarity required for conveying the bigger picture, yet was perceived as most useful for early project stages. Our contribution to the body of literature is that we compare the technology acceptance of new and existing scheduling methods in order to unearth their complementary roles. This work is important for managers deciding on a combination of planning tools, enabling them to better run their projects.